Gallic acid melanin pigment hydrogel as a flexible macromolecule for articular motion sensing - Park, Seo A.; Yeo, Chan Seo; Jung, Wonjong; Choi, Kwon Young (New Biotechnology, 2024)
In this study, water-soluble melanin was synthesized through the genetic recombination of Escherichia coli using gallic acid as a substrate. The recombinant host produced 2.83 g/L of gallic acid-based melanin (GA melanin) from 20 mM gallic acid. Notably, the isolated GA melanin demonstrated exceptional antioxidant and antimicrobial activities, exhibiting a 25.7 % inhibition ratio against Candida albicans. The structure and composition of GA melanin were analyzed using Fourier-transform infrared (FT-IR) spectroscopy, scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDS), and X-ray diffraction (XRD). Remarkably, GA melanin displayed high thermal stability, maintaining integrity up to 1000 °C. Additionally, it exhibited unique electrical properties in terms of conductivity and resistivity compared to other common types of melanin. Subsequently, GA melanin was cross-linked with hydrogel to create a sensing template. The resulting GA melanin hydrogel demonstrated lower resistance (80.08 ± 3.0 kohm) compared to conventional hydrogels (108.62 ± 10.4 kohm), indicating an approximately 1.77-fold improvement in adhesion. Given its physical, biological, and electrical properties, the GA melanin hydrogel was further utilized as a flexible motion-sensing material to detect resistivity changes induced by knee, wrist, and finger bending, as well as vocal cord vibrations. In all cases, the sensing module displayed notable sensitivity to motion-induced resistivity variations.
Keywords: Gallic acids; Genetic recombinations; Melanin pigments; Motion sensing; Motion sensors; Property; Recombinant hosts; Resistivity; Synthesised; Watersoluble; Antioxidants; Candida albicans; Escherichia coli; Gallic Acid; Hydrogels; Melanins; Conductive material; Gallic acid; Hydrogel; Melanin; Motion sensor; Resistivity